Single-Cell Phenotypic Characterization of Human Pituitary GHomas and Non-Functioning Adenomas Based on Hormone Content and Calcium Responses to Hypothalamic Releasing Hormones - Senovilla, Laura; Núñez, Lucía; de Campos, José María; de Luis, Daniel A.; Romero, Enrique; García-Sancho, Javier; Villalobos, Carlos (Frontiers in Oncology, 2015)
Human pituitary tumors are generally benign adenomas causing considerable morbidity due to excess hormone secretion, hypopituitarism and other tumor mass effects. Pituitary tumors are highly heterogeneous and difficult to type, often containing mixed cell phenotypes. We have used calcium imaging followed by multiple immunocytochemistry to type growth hormone secreting (GHomas) and non-functioning pituitary adenomas (NFPAs). Individual cells were typed for stored hormones and calcium responses to classic hypothalamic releasing hormones (HRHs). We found that GHomas contained GH cells either lacking responses to HRHs or responding to all four HRHs. However, most GHoma cells were polyhormonal cells responsive to both TRH and GHRH. NFPAs were also highly heterogeneous. Some of them contained ACTH cells lacking responses to HRHs or polyhormonal gonadotropes responsive to LHRH and TRH. However, most NFPA were made of cells storing no hormone and responded only to TRH. These results may provide new insights on the ontogeny of GHomas and NFPAs.